Descriptions of four new species of Thysanophrys (Scorpaeniformes: Platycephalidae) from the Western Indian Ocean - Knapp, Leslie W. (Zootaxa, 2013)
Four new species of Thysanophrys are described from the Western Indian Ocean (WIO). T. rarita, known from a single specimen taken off Somalia, is provisionally placed in Thysanophrys and is distinguished by its color pattern and number of preocular and suborbital spines. T. tricaudata is described from three specimens taken at SCUBA stations off southwestern Sri Lanka. They differ from other western Indian Ocean (WIO) Thysanophrys in color pattern, lack of ocular flaps, number of dorsal fin spines and scale counts. The remaining two new species are somewhat similar to the widespread Indo-Pacific species, T. chiltonae Schultz (1966). T. randalli is described from specimens taken at the Amirante Islands and Mauritius. It may also be widespread in the Indo-Pacific, but differs from T. chiltonae in nasal spine structure, color pattern, type of iris lappet margin, and in having a much shorter maximum size. T. springeri also appears to be a smaller species than T. chiltonae and, aside from one record off Djibouti, is restricted to Red Sea. It also differs from T. chiltonae in color pattern, in having fewer pectoral rays and fewer scale rows between the second dorsal-fin insertion and the lateral line. Although T. chiltonae is relatively common in the northern Indian Ocean, it does not appear to have entered the Red Sea.